Inter/multi/trans-disciplinarity : The Challenge for Publishing - Žic Fuchs, Milena (2014)
HORIZON 2020 – The EU Framework Programme for Research and Innovation introduces the notion of the so-called Grand Challenges (original terminology), now in the final documents called Societal Challenges. The main push of the new Framework for Research and Innovation is towards addressing major issues that confront Europe, the European citizen, but at the same time they aim to tackle global issues, such as health, demographic change and wellbeing ; food security, sustainable agriculture and forestry, marine, maritime and inland water research and bioeconomy ; secure, clean and efficient energy ; smart, green and integrated transport ; climate action, environment, resource efficiency and raw materials ; Europe in a changing world – inclusive, innovative and reflective societies ; and secure societies – protecting freedom and security of Europe and its citizens. The Societal Challenges on one hand cover the huge span from the individual to the global dimension. On the other, they are implicitly inter/multi/transdisciplinary. It follows that research results (hopefully) will transcend disciplinary boundaries and achieve the aims of HORIZON 2020 in the sense of “solving” the Grand Challenges. What does this mean for the future of publishing research results? In another words, a new challenge surfaces in the question of where, in which journals, will researchers publish “interdisciplinary” articles? If the results of HORIZON 2020 will truly be inter/multi/transdisciplinary, will the existing array of journals be ready to accept papers that go beyond the boundaries of their usually disciplinary orientation? Over the last decades, in many disciplines throughout the different domains of research, we have witnessed the appearance of journals that deal with specialized sub-disciplines or even specialized topics. This development was in accordance with the inherent development of the disciplines themselves, however, will “specialized” journals in the future open up their doors to articles written by a combination of scholars from, for example, chemistry, environmental history and engineers of different kinds? And it is not a matter of the authors, it will be the approach and the cross-domain content of articles that will pose questions to editors. Articles dealing with any topic within the Grand Challenges may be faced with new “rules” and a complex peer review context. How ready and willing are editors and editorial boards to adapt to this new situation? An example will be provided and the experience gained from the ESF Junior Summit “Water: Unite and Divide”, an experiment in vivo of bringing together 36 early-career researchers on a topic which does not have a history (at least not one that is recognized amongst the domains involved) of inter/multi/transdisciplinary research. Outcomes of this event were manifold, but one of the most interesting ones was the joined research amongst the young scholars from different domains that evolved after the event itself, was the attempt of publishing these results. In the end, the results appeared as an open-access variant of Journal of Water Resource and Protection (http://www.scirp.org/journal/jwarp/). In the new publishing landcape, will developments go in the direction of open-access journals becoming the main outlets for inter/multi/transdisciplinary research results? Will this induce a different balance between the open-access journal arena and the “traditional” journal publications? The above are just a few of the questions that will (or already have) arise within the HORIZON 2020 challenge for publishing.
Projekt MZOS
ENG